2004
DOI: 10.1038/nn1260
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ion channel localization and phosphorylation by neuronal activity

Abstract: Voltage-dependent Kv2.1 K(+) channels, which mediate delayed rectifier Kv currents (I(K)), are expressed in large clusters on the somata and dendrites of principal pyramidal neurons, where they regulate neuronal excitability. Here we report activity-dependent changes in the localization and biophysical properties of Kv2.1. In the kainate model of continuous seizures in rat, we find a loss of Kv2.1 clustering in pyramidal neurons in vivo. Biochemical analysis of Kv2.1 in the brains of these rats shows a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
538
5
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(596 citation statements)
references
References 40 publications
45
538
5
8
Order By: Relevance
“…kainate-induced seizures in vivo and brief glutamate exposures in vitro). 27 This channel declustering appears to be correlated to calcium-dependent dephosphorylation of the channel and does not seem to affect surface expression. As the apoptotic current surge requires activation of the MAPK p38 pathway, 4 we believe that an initial phosphorylation event is responsible for the upregulation of Kv2.1 surface expression during apoptosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…kainate-induced seizures in vivo and brief glutamate exposures in vitro). 27 This channel declustering appears to be correlated to calcium-dependent dephosphorylation of the channel and does not seem to affect surface expression. As the apoptotic current surge requires activation of the MAPK p38 pathway, 4 we believe that an initial phosphorylation event is responsible for the upregulation of Kv2.1 surface expression during apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…At 3 h after treating Myc-Kv2.1-expressing CHO with either vehicle or DTDP (25 mM, 5 min), cells were incubated with 2 mg/ml sulfo-NHS-SS-biotin, and solubilized in 1% Triton, 0.1% SDS. Biotinylated proteins were isolated with immobilized neutravidin as described by Misonou et al 27 Immunoblotting with antiMyc and GAPDH antibodies were used to analyze protein abundance in the total lysate and isolated surface fractions.…”
Section: Biotinylation Of Membrane Proteinsmentioning
confidence: 99%
“…2 a). As a control we examined the phosphorylation state of Kv2.1, which is regulated by NMDA-dependent activation of calcineurin (Misonou et al, 2004), and found that bath application of FK506/CSA attenuated the effect of NMDA (Fig. S2).…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…Relative to other Kv channels, Kv2.1 exhibits a high threshold for activation (+10-20 mV activation midpoint) and primarily regulates excitability during periods of high-frequency firing in pyramidal cells (3,6) or tonic firing in sympathetic neurons (7). The threshold for activation of Kv2.1 is shifted to more negative potentials in response to various excitatory stimuli (e.g., glutamate, ischemia, muscarinic activation, elevated cytoplasmic Ca 2+ ); it is presumably via this mechanism that Kv2.1 selectively regulates neuronal excitability during periods of high-frequency excitotoxic stimuli (8)(9)(10). Kv2.1 also plays a well-established role in apoptosis (11), where it may mediate the KCl loss involved in cell death.…”
mentioning
confidence: 99%
“…One of the hallmarks of Kv2.1 expression in mammalian neurons is specific targeting to large, high-density cell surface clusters restricted to the soma and proximal dendrites (8,12,13). Interestingly, not only is channel voltage dependence altered by the aforementioned stimuli, but also channel localization.…”
mentioning
confidence: 99%